Game Edukasi Dalam Pembelajaran Seni Rupa Memanfaatkan Metode Scramble Berbasis Android - Reka Purnama Sari; Fera Damayanti; khairunnisa (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
The progress of Fine Arts Learning is one type or field of education recommended by the curriculum, in the finearts curriculum there are several main lessons or pictures. In this study, there were problems in learning art,previously in learning art it was still boring by working on predetermined images, therefore it is necessary tohave an entertaining learning method that can be applied to developing technology, one of the learning methodsthat can increase student activity is the Scramble method. Scramble is an inspiring picture stacking game to addactivity. The resulting Scramble method is a simple game about randomizing images using the Android-basedscramble method. The application was built using C# programming and Unity 3D software.